Formation of primary school children self esteem on the basis of criteria-based assessment - A. D. Syzdykbayeva; R. K. Izmagambetova; A. S. Amirova; T. B. Bainazarova; M. K. Sadykova (Russian State Vocational Pedagogical University, 2021)
Introduction. The ongoing socio-economic transformations in society and science education actualise the modern educational policy in the field of personality formation of students who are capable of self-development and self-realisation. In these conditions, the primary school provides an integral system of knowledge, skills, and experience of independent activity and personal responsibility of students. The article deals with the problem of development of self-esteem in primary school children.Aim. The aim of this research was to investigate the relationship between self-esteem and academic performance among primary school children.Methodology and research methods. The present research is based on systemic, personal, axiological, and activity methodological approaches. The article includes the study of the types of self-esteem of primary school children, and the level of aspirations. 107 school pupils participated in the research. At the ascertaining stage, diagnostics of the level of formation of self-esteem of younger schoolchildren was carried out. A number of pedagogical conditions to improve the cognitive, evaluative, and behavioural components were implemented at the training stage of the research.Results. The authors define the following concepts: self-assessment, types of self-assessment, self-assessment of primary school children, the level of claims, and criteria assessment. The programme of diagnostics of the level of formation of self-esteem of primary school children is presented. The indicators (cognitive, evaluative, and behavioural) and levels of formation of self-esteem of the primary school children (low, adequate, overestimated) are defined. The article presents the results of experimental work on the implementation of pedagogical conditions (including primary school children in the process of self-knowledge; gradual involvement of primary school children in self-assessment and reflexive activities; participation of primary school children in the formation of criteria-based assessment) to increase the level of self-esteem of primary school children.Scientific novelty. The pedagogical conditions, which contribute to the self-esteem of primary school children, are presented for the first time.Practical significance. The materials of the article are of practical value for teachers engaged in the development of lectures, seminars, assignments for independent work.